2023
DOI: 10.1007/s13311-023-01437-6
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Dependent Reduction of Cybersickness in Virtual Reality by Transcranial Oscillatory Stimulation of the Vestibular Cortex

Alberto Benelli,
Francesco Neri,
Alessandra Cinti
et al.

Abstract: Virtual reality (VR) applications are pervasive of everyday life, as in working, medical, and entertainment scenarios. There is yet no solution to cybersickness (CS), a disabling vestibular syndrome with nausea, dizziness, and general discomfort that most of VR users undergo, which results from an integration mismatch among visual, proprioceptive, and vestibular information. In a double-blind, controlled trial, we propose an innovative treatment for CS, consisting of online oscillatory imperceptible neuromodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The researchers concluded that while various models for detecting cybersickness have been developed, there is no model to predict early adverse events in VEs. Future, more accurate and effective ML approaches will undoubtedly be inspired by current knowledge of how the brain works, as well as the new brain/organism models/approaches being developed and linking them to these bio-digital frontiers ( Benelli et al, 2023 ; Daşdemir, 2023 ; Yang et al, 2023 ). These and similar studies ( Chang et al, 2023 ; Souchet et al, 2023 ) indicate, as does our research, that we are still at the beginning of understanding the potentially beneficial and detrimental effects of digital worlds on their users, especially older adults ( Drazich et al, 2023 ; Séba et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers concluded that while various models for detecting cybersickness have been developed, there is no model to predict early adverse events in VEs. Future, more accurate and effective ML approaches will undoubtedly be inspired by current knowledge of how the brain works, as well as the new brain/organism models/approaches being developed and linking them to these bio-digital frontiers ( Benelli et al, 2023 ; Daşdemir, 2023 ; Yang et al, 2023 ). These and similar studies ( Chang et al, 2023 ; Souchet et al, 2023 ) indicate, as does our research, that we are still at the beginning of understanding the potentially beneficial and detrimental effects of digital worlds on their users, especially older adults ( Drazich et al, 2023 ; Séba et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Benelli et al 2023 [54] Researchers emphasize that there is not yet an effective solution to the problem of cybersickness (CS) and propose an innovative approach for a frequency-dependent reduction in CS in VR via transcranial oscillatory stimulation of the vestibular cortex. The authors indicate that the new approach may be used to treat a variety of vestibular dysfunctions.…”
Section: Applications Of Ves Authors Descriptions Of Vr Approaches Ba...mentioning
confidence: 99%
“…In addition, VEs are increasingly being incorporated into research and evaluation of natural aging processes or effective support in (neuro)geriatric care (e.g., preventing falls or improving cognitive function in the elderly) [21,70,71]. Model studies with healthy participants are important and interesting in evaluating/testing new technologies [4,28,29,[54][55][56].…”
Section: Hinze Et Al 2021 [76]mentioning
confidence: 99%
See 1 more Smart Citation